2015
DOI: 10.1094/phyto-09-14-0253-r
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of the Indian Populations of ‘Candidatus Liberibacter asiaticus’ Based on the Tandem Repeat Variability in a Genomic Locus

Abstract: Citrus huanglongbing (HLB, citrus greening disease) is an extremely destructive disease affecting citrus and causes severe economic loss to the crop yield worldwide. The disease is caused by a phloem-limited, noncultured, gram-negative bacteria Candidatus Liberibacter spp., the widely present and most destructive species being 'Candidatus Liberibacter asiaticus'. Although the disease has been reported from almost all citrus growing regions of India, knowledge on the molecular variability of the pathogen 'Ca. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 24 publications
1
25
1
1
Order By: Relevance
“…mandarins (Khasi mandarin) were predominantly infected by TRN7 and TRN9 genotypes. In previous study preferential accumulation of TRN5 and TRN9 was reported form mandarins (Ghosh et al, 2015). Sweet oranges in NE region were more frequently infected with CLas of TRN7, whereas preferential accumulation of TRN6 was detected earlier from sweet oranges grown in other parts of India (Ghosh et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…mandarins (Khasi mandarin) were predominantly infected by TRN7 and TRN9 genotypes. In previous study preferential accumulation of TRN5 and TRN9 was reported form mandarins (Ghosh et al, 2015). Sweet oranges in NE region were more frequently infected with CLas of TRN7, whereas preferential accumulation of TRN6 was detected earlier from sweet oranges grown in other parts of India (Ghosh et al, 2015).…”
Section: Discussionmentioning
confidence: 76%
“…The CLas population previously characterized from the other parts of India (Ghosh et al, 2015) were compared with the strains characterized in the present study in order to have overall picture of its genetic structure. In the NE states of India, where citrus is largely cultivated through seedling propagation but budded plants are less commonly planted, the CLas genotypes of TRN7 were more predominant (23.75% frequency) followed by TRN5 genotypes (15.00% frequency) (Table 2), which indicated that overall infection of class II genotypes of CLas were widely prevalent in the citrus groves of NE India.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations